The Health Ethical Dilemmas Caused by Financial Toxicity of Patients with Critical Diseases and Suggested Countermeasures - Zhengjun WANG; Wenlong JIANG; Jianqin CAO (Yixue yu zhexue)
The issue of financial toxicity faced by patients with major diseases is becoming increasingly severe, leading to ethical conflicts with individual health rights and triggering health ethics dilemmas. These dilemmas mainly include the conflicts between unclear treatment costs and medical decision-making, the tension between seeking help and protecting privacy, the misalignment between medical expenses and inadequate health insurance policies, the imbalance between the medical assistance needs and the scarcity of aid programs, the conflict between impaired work capacity and the challenge of increasing income, as well as the heavy burden on caregivers versus their caregiving responsibilities. It is essential to engage in cost discussions and shared decision-making, assist patients with disease-related financial planning, strengthen disease prevention and public health education, expand financial assistance programs, promote the equitable distribution of medical resources, reduce family burdens, and ensure patients' employment and return to work. These measures aim to alleviate financial toxicity and safeguard the health rights of patients with severe and major diseases.